'COME TO HOLLAND': PROMOSI PARIWISATA BELANDA BAGI HINDIA-BELANDA DAN INDONESIA - Achmad - Sunjayadi (Jurnal Kajian Wilayah, 2017)
Relation between Indonesia and The Netherlands, particularly in the tourism sector has been established long time ago. The relation has been built since Indonesia still part of Dutch colony until now. Relation in the tourism sector had disconnected between the beginning of Second World War until the 1950s. This article tries to trace the relation and the contemporary situation of the tourism sector in Netherland. The discussion focuses on the Netherlands as a tourism destination for the Dutch East Indies’ verlofgangers (those who furlough) and for Indonesian tourists. The question is how Netherlands promote their country as tourist destination and the reason why they promote their country to Dutch East Indies and Indonesian tourists. The data sources for this article are from Dutch’s newspapers and magazines during the colonial period, archives of tourism agencies in the Netherlands as well as Dutch contemporary newspapers,.Keywords: The Netherlands, Indonesia, Dutch East Indies, tourism, promotionAbstrakHubungan antara Indonesia dengan Belanda dalam sektor kepariwisataan sudah terjalin lama. Hubungan tersebut terjalin sejak Indonesia masih Hindia-Belanda dan berada di bawah kepemimpinan Belanda hingga Indonesia merdeka. Hubungan di sektor kepariwisataan itu sempat terputus pada masa awal Perang Dunia II hingga tahun 1950-an. Artikel ini membahas jejak hubungan dan situasi kontemporer sektor kepariwisataan di kedua negara. Bahasan dititikberatkan pada Belanda sebagai negara tujuan wisata bagi penduduk Hindia Belanda yang ketika itu disebut verlofgangers (orang yang mengambil cuti) dan wisatawan Indonesia pada saat ini. Pertanyaan yang akan dijawab pada studi ini adalah bagaimana Belanda mempromosikan negerinya serta alasan di balik promosi itu. Sumber yang digunakan adalah arsip surat kabar dan majalah pada periode tersebut, arsip dari lembaga pariwisata di Belanda. serta surat kabar kontemporer terbitan Belanda.Kata kunci: Belanda, Indonesia, Hindia-Belanda, kepariwisataan, promosi